The Role of Motivation and Leadership Style in Increasing Employee Work Productivity at PT. Andalan Mandiri Busana Boyolali - Lestari, Ina; Sulistyowati, Pemilia (Pusat Riset dan Inovasi Nasional, 2025)
The purpose of this study is to test and analyze the effect of work motivation and leadership style on employee productivity at PT. Andalan Mandiri Busana Boyolali. The focus of the study is directed at the sewing division which has a crucial role in the production process. The method approach in this study is quantitative explanatory. This study involved 100 respondents from employees of PT. Andalan Mandiri Busana Boyolali who were selected using purposive sampling techniques based on certain criteria. Data collection was carried out through a Likert-based questionnaire, then the data was analyzed through multiple linear regression tests with SPSS 25 software. The results of the analysis showed that work motivation had a positive and significant effect on employee productivity. Likewise, leadership style contributed significantly to improving workforce performance. Together, all independent variables have a major effect on increasing the productivity of the company's workforce. The results of the statistical test showed that the coefficient of determination (R²) had a fairly high value, indicating that the variables of work motivation and leadership style were able to explain most of the variability in employee productivity. Furthermore, recommendations for management are to develop strategies to increase motivation and implement an adaptive and participatory leadership style to increase work efficiency and effectiveness in the company environment.